Optimizing the particle size distribution of heat-treated boron derivative wastes in cement mortars as portland cement replacements. (3rd May 2021) - Koroglu, Levent; Over Kaman, Derya; Ayas, Erhan
Highlights: Ground heat-treated boron derivative wastes (HTBDWs) replaced with Portland cement. Phase analysis of aged pastes showed that HTBDWs were non-reactive against water. 94.5% of reference mortar's compressive strength was obtained with broader HTBDW. Much higher particle size range of HTBDW caused high strength loss (42.5%). Not only median particle size but also particle size range affected packing density. Abstract: Heat-treated boron derivative wastes (HTBDWs) having three different particle size distributions (PSDs) were used as Portland cement replacements by 25 wt%. In contrast to hypothesis, the smaller median particle size of HTBDW compared to cement decreased the strength of mortars because of lower packing density. The compositions and microstructures of hydration products were similar for all mortars. The higher particle size range of HTBDW reduced strength as only as 6.3% of that of reference mortar. Briefly, applicable cement mortars can be produced by slightly broadening of PSD of non-reactive fillers as cement replacements thanks to their contribution to packing density.